Analysis of PVD Installation Methods Due to Limited Vertical Clearance in the Lamongan North Ring Road Construction Project Section 1 STA 0+400 to STA 0+426 - Barimbing, Fanny Rumintha Br; Lastiasih, Yudhi; Wahyudi, Herman; Udukha, Sifa` (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The construction of the Lamongan North Ring Road is planned to be built on soft soil. Based on the results of the soil investigation, it is known that the subgrade condition is classified as soft to very soft soil with a depth of 18 meters. One of the problems of this very soft soil is the settlement. Therefore, the National Road Implementation Agency of East Java - Bali Region conducted subgrade improvement using preloading combined with Prefabricated Vertical Drain (PVD). The configuration of the PVD installation is 18 meters deep with a triangular pattern and the distance between PVDs is 1 meter. To stake the PVDs 18 meters deep, a piling rig with a minimum height of 24 meters is required. In the STA 0+400 to STA 0+426 section there is a 150 kV Lamongan - Paciran High Voltage Air Line (SUTT) cable crossing the road with a conductor to platform distance of 18 meters. The existence of this cable is a challenge in the PVD driving as deep as 18 meters. Therefore, this journal will analyze the PVD piling implementation method that can be carried out in this segment. The method carried out in this study is to start with the collection of secondary data such as shop drawings as a reference for the implementation of work in accordance with the planned design. Based on the design plan, an implementation method that can be applied to limited vertical clearance conditions is obtained. Based on the results of the research, an 18-meter deep PVD installation method was obtained that can be applied to limited vertical clearance conditions in the Lamongan North Ring Road construction project Section 1 STA 0+400 to STA 0+426. In addition, it was also found that the time required was 34.75 minutes to stake 1 PVD point using the pulled hole PVD method.